2022
DOI: 10.1093/tropej/fmac059
|View full text |Cite
|
Sign up to set email alerts
|

Prediction Model for Severe Mycoplasma pneumoniae Pneumonia in Pediatric Patients by Admission Laboratory Indicators

Abstract: Objective The purpose of this study was to develop a model for predicting severe Mycoplasma pneumoniae pneumonia (SMPP) in pediatric patients with Mycoplasma pneumoniae pneumonia (MPP) on admission by laboratory indicators. Methods Pediatric patients with MPP from January 2019 to December 2020 in our hospital were enrolled in this study. SMPP was diagnosed according to guideline for diagnosis and treatment of community-acquir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…In addition, the study suggested that ESR might be an indicator among a combination of laboratory parameters to predict the severe form of M. pneumoniae infection. [ 21 ] The M. pneumoniae infection of pediatric KD patients might lead to a more severe tendency due to the predisposing trait of immune function alterations in pediatric KD patients. Therefore, the hemoglobin and ESR might be important indicators to identify the M. pneumoniae infection in pediatric KD patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the study suggested that ESR might be an indicator among a combination of laboratory parameters to predict the severe form of M. pneumoniae infection. [ 21 ] The M. pneumoniae infection of pediatric KD patients might lead to a more severe tendency due to the predisposing trait of immune function alterations in pediatric KD patients. Therefore, the hemoglobin and ESR might be important indicators to identify the M. pneumoniae infection in pediatric KD patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, because all of the retrieved studies were performed in China and the severity of ADVP was evaluated according to the Chinese guidelines, we therefore used these criteria in our meta-analysis accordingly. Specifically, a severe ADVP was diagnosed based on the criteria of the 2019 Chinese Guideline for the Diagnosing and Management of Children with Community-Acquired Pneumonia ( 40 ) if any of the following criteria were met: (1) Overall poor health condition of a patient. (2) A conscious disturbance.…”
Section: Methodsmentioning
confidence: 99%
“…However, complex ML methods can manage a broader array of variables, often yielding more accurate and precise results than traditional modeling methods 21 . Additionally, one of the main challenges in applying MPP prediction models to clinical practice is the lack of external validation [19][20][21][22] .…”
Section: Introductionmentioning
confidence: 99%